Prospective Surveillance of Healthcare-Associated Infections in Residents in Four Long-Term Care Facilities in Graz, Austria - Elisabeth König; Mara Medwed; Christian Pux; Michael Uhlmann; Walter Schippinger; Robert Krause; Ines Zollner-Schwetz (MDPI AG, 2021)
Healthcare-associated infections (HCAI) are a common cause for residents' mortality and morbidity associated with a significant socio-economic burden. Data on HCAIs in Austrian long-term care facilities are scare. Therefore, we evaluated the incidence rate of HCAIs per 1000 resident days in four LTC facilities in Graz, Austria, characterized the spectrum of HCAIs and the use of antimicrobial substances. We conducted a prospective surveillance study from 1 January to 31 December 2018 in four LTCFs of the Geriatric Health Centre of the City of Graz (total of 388 beds). Nursing staff collected data on HCAIs once a week using an electronic reporting system. During the 12-month surveillance period, 252 infections of 165 residents were recorded. The overall incidence rate of HCAIs was 2.1 per 1000 resident days. Urinary tract infections were the most commonly recorded HCAIs (49%, 124/252, 1.03 per 1000 resident days), followed by skin and soft tissue infections and respiratory tract infections. Beta-lactams (ATC class J01C) were prescribed most frequently (63/212), followed by fluoroquinolones (J01M; 54/212). In conclusion, the overall incidence rate for HCAIs was relatively low at 2.1 per 1000 resident days. Our real-life data can serve as a basis for future antimicrobial stewardship and infection prevention interventions.